Comparative Evaluation of the Chemical, Physical and Microbiological Characteristics of Beef and Ostrich Meat Burger - Elhashmi, Yasir Hilal Abdalla; M. Z., Eskander; S. Y., Falih; M. E., Abdalmageed; E. Hassan, Hassan (Gezira Journal of Agricultural Science; Vol 19 No 2 (2021), 2023)
Ostrich meat is gradually becoming recognized as an alternative to red meat now a days. The main objectives of this study were to evaluate the quality characteristics of burger processed from the meat of ostrich and beef, to investigate the existence of microbial growth on a burger from the meat of ostrich and beef as well as possible environmental contaminants. The Ostrich and beef meat were prepared and stored frozen. The burger was processed in the laboratory and analyzed for chemical composition (crude protein, moisture, fat, and ash). Physical properties (water holding capacity, cooking loss) and microbiological analysis were done also. The findings of this study revealed that chemical composition of burgers from ostrich and beef had highly significant differences (p≤ 0.01) in moisture content, crude protein, lipids, and ash among all products. The physical attributes of burgers revealed that there were highly significant differences (p≤0.01) among all types of products. The Burger microbiological showed that there were highly significant differences (p≤0.01) in all parameters without E. coli and pseudomonas, which had no significant differences (NS) among all types of burgers. The study recommended that ostrich meat can be used  as an alternative to beef meat.